Automation turning manufacturing sector on its head - Hidalgo, Vanessa A.
The urgent need to increase productivity has made manufacturing firms around the world turn to technology, thus ushering the global shift to further automation.
Keywords: Universal Robots; Collaborative robots; Cobots; Robotic arms; Robotics